20(S)-protopanaxadiol inhibits proliferation and induces apoptosis of acute myeloid leukemia cells via targeting Bcl-XL and MCL-1 - Meng Xu; Meng Xu; Meng Xu; Feng Hao; Shuangshuang Wu; Zhanning Qu; Zhanning Qu; Junying Li; Shuang Chen; Fang Fang; Yundong Zhao; Cheng Hu (Frontiers in Pharmacology)
Currently, intensive chemotherapy with cytarabine and anthracycline (the “7 + 3” regimen) and hypomethylating agents remains the standard treatment for patients with acute myeloid leukemia (AML). Despite advances in treatment such as targeted therapies, patient outcomes remain unsatisfactory due to adverse drug reactions, susceptibility to drug resistance, and high recurrence rates. Consequently, there is an urgent need to develop safer and more efficacious treatments for AML. In this study, we examined the effects of 20(S)-protopanaxadiol (20(S)-PPD) on AML cells. Our findings indicate that 20(S)-PPD inhibits cell proliferation and induces apoptosis in AML cells. Mechanistically, 20(S)-PPD-induced apoptosis was at least partially dependent on the anti-apoptotic proteins MCL-1 and Bcl-XL. Moreover, the downregulation of MCL-1 and Bcl-XL by 20(S)-PPD is mediated through the inhibition of transcription and a decrease in protein stability. Additionally, results from virtual molecular docking demonstrated that 20(S)-PPD exhibits lower binding energies with MCL-1 and Bcl-XL (−7.58 and −8.75 kcal/mol, respectively), suggesting that 20(S)-PPD may directly interact with these proteins, thereby accelerating their degradation. Finally, 20(S)-PPD has been shown to synergistically enhance the anti-leukemic activity of venetoclax, a selective Bcl-2 inhibitor, in AML cells. The current study suggests that the continued development of 20(S)-PPD as a therapeutic agent for AML would be advantageous.